Drift-diffusion of highly mobile dopants in CdTe - Wolf, Herbert; Wagner, Florian; Kronenberg, Jörg; Wichert, Thomas; Grill, Roman; Belas, Eduard (Diffusion Fundamentals, 2008)
The diffusion of Ag in CdTe exhibits anomalous concentration profiles, which essentially reflect the profile of the deviation from stoichiometry. At a diffusion temperature of about 800 K, the Ag dopant atoms are present as charged interstitials. The deviation from stoichiometry at diffusion temperature substantially changes upon an external source of Cd atoms. Such an external source can be represented either by the vapor pressure from metallic Cd or by a Cd layer arising at the interface to an evaporated layer of Cu or Au. Also, the Co diffusion in CdZnTe is shown to be strongly affected by the presence of an external vapor pressure of Cd, but in a substantially different way compared to the Ag diffusion in CdTe.